Epistylis smalli (Ciliophora: Peritrichia) a new peritrich from Guaiba Lake, Southern Brazil - Utz, Laura R. P.; Santos, Mariana Silva Dos; Araujo, Gabriella Oliveira De (Zootaxa, 2015)
Epistylis smalli n. sp., a freshwater colonial peritrich, was collected in Guaíba Lake, Southern Brazil. Its morphology was investigated using in vivo observations and protargol stained specimens. E. smalli possess an elongate zooid that measures in vivo, on average, 173 μm in length and 50 μm in width. A C-shaped macronucleus that surrounds the infundibulum and a single contractile vacuole could be easily observed in the living cell. The oral infraciliature observed in silver-stained specimens was typical of peritrich ciliates, with three infundibular polykinetids bearing three rows of kinetosomes. A detailed description of the live and stained zooids is given.